ANALISIS PEMILIHAN TEMPAT PENYIMPANAN DATA SECARA ONLINE MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS - Budi Wasito, S.Kom., MM., M.kom (Jurnal Informatika dan Bisnis, 2018)
In this era of rapidly evolving technology is the speed and accuracy of the information has a huge influence. The use of online data storage or the so-called Cloud Computing becomes one of the important tools in our daily lives and in the business world. Ease given to the user is an essential in everyday life easier.The storage site selection analysis using Analytical Hierarchy Process (AHP) as a method of decision support systems. Expert Choice 11 is a software that helps structuring and calculating model of decision-making in this technique. This study uses data collection methods such as questionnaires filled out by the user online data storage in everyday life. The results of this study is to provide information to the public in determining where online data storage is the best in a variety of criteria. The conclusion of this study is Analytical Hierarchy Process ( AHP ) gives the results of calculations , where the results can assist the community in determining the selection of online data storage that get the final result , namely Dropbox as an online storage place that has been chosen community. Keywords: analysis, Analytical Hierarchy Process (AHP), cloud computing, data storage online